ANALYSIS OF STUDENTS’ ENGLISH VOCABULARY MASTERY THROUGH FLASHCARD MEDIA AT THE SEVENTH GRADE OF SMP NEGERI 1 HILIDUHO - ZEBUA, INDAH RATNA; ZEGA, RISWAN; TELAUMBANUA, YASMINAR AMAERITA; WARUWU, YAREDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Vocabulary plays a crucial role in language acquisition, impacting all language skills including listening, speaking, reading, writing, digital literacy, and self- regulation. Observations conducted at SMP Negeri 1 Hiliduho revealed that some students encounter challenges in mastering the necessary vocabulary and comprehending lessons. The limited variety of learning media resulted in diminished student interest in the learning process. This study aimed to analyzing the use of flashcard media in increasing students' vocabulary mastery and why flashcard media can improve students' vocabulary mastery at the seventh grade of SMP Negeri 1 Hiliduho. The method used in this research was qualitative method. To obtain data, researcher used two data collection techniques, namely observation and interview. After obtaining the data, the researcher analyzed the data using the theory of Miles and Huberman in (Santy. 2021), namely reducing, displaying, and concluding data. The results of the study were showed. In the first meeting, the average score of students' vocabulary mastery was 64, which was categorized as “enough.” In the second meeting, the average student score was 77.6, categorized as “good,” and in the third meeting the average student score reached 90, categorized as “very good”. The results of this study show that there is a clear development in students' vocabulary mastery through flashcard media, because based on the results of student and teacher interviews found by researcher in the field show that the advantages of flashcards media were portability, practicality, memorability, and engagement so that students were interested in learning. Based on these results, it can be concluded that students in the seventh grade at SMP Negeri 1 Hiliduho demonstrate enhanced mastery of English vocabulary through the use of flashcard media. Consequently, it is recommended that teachers incorporate flashcard media in vocabulary instruction to further cultivate students' interest and proficiency in vocabulary learning. ABSTRAKKosakata memainkan peran penting dalam penguasaan bahasa, yang berdampak pada semua keterampilan bahasa termasuk mendengarkan, berbicara, membaca, menulis, literasi digital, dan pengaturan diri. Pengamatan yang dilakukan di SMP Negeri 1 Hiliduho menunjukkan bahwa beberapa siswa mengalami kesulitan dalam menguasai kosakata yang diperlukan dan memahami pelajaran. Terbatasnya variasi media pembelajaran mengakibatkan berkurangnya minat siswa dalam proses pembelajaran. Penelitian ini bertujuan untuk menganalisis penggunaan media flashcard dalam meningkatkan penguasaan kosakata siswa dan mengapa media flashcard dapat meningkatkan penguasaan kosakata siswa di kelas tujuh SMP Negeri 1 Hiliduho. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Untuk memperoleh data, peneliti menggunakan dua teknik pengumpulan data, yaitu observasi dan wawancara. Setelah mendapatkan data, peneliti menganalisis data dengan menggunakan teori Miles dan Huberman dalam (Santy. 2021), yaitu mereduksi, mendisplay, dan menyimpulkan data. Hasil dari penelitian yang dilakukan menunjukkan. Pada pertemuan pertama, nilai rata-rata penguasaan kosakata siswa adalah 64, yang dikategorikan sebagai “cukup.” Pada pertemuan kedua, nilai rata-rata siswa adalah 77,6 yang dikategorikan “baik,” dan pada pertemuan ketiga nilai rata-rata siswa mencapai 90 yang dikategorikan “sangat baik.” Hasil penelitian ini menunjukkan bahwa ada perkembangan yang jelas dalam penguasaan kosakata siswa melalui media flashcard, karena berdasarkan hasil wawancara siswa dan guru yang ditemukan oleh peneliti di lapangan menunjukkan bahwa kelebihan media flashcard adalah portabilitas, kepraktisan, mudah diingat, dan menarik sehingga siswa tertarik untuk belajar. Berdasarkan hasil tersebut, dapat disimpulkan bahwa siswa kelas VII di SMP Negeri 1 Hiliduho menunjukkan peningkatan penguasaan kosakata bahasa Inggris melalui penggunaan media flashcard. Oleh karena itu, disarankan agar guru memasukkan media flashcard dalam pengajaran kosakata untuk lebih menumbuhkan minat dan kemahiran siswa dalam pembelajaran kosakata.